Understanding current and projected emergency department presentations and associated healthcare costs in a changing thermal climate in Adelaide, South Australia. Issue 6 (4th April 2022) - Wondmagegn, Berhanu Yazew; Xiang, Jianjun; Dear, Keith; Williams, Susan; Hansen, Alana; Pisaniello, Dino; Nitschke, Monika; Nairn, John; Scalley, Ben; Xiao, Alex; Jian, Le; Tong, Michael; et al.
Abstract : Background: Exposure to extreme temperatures is associated with increased emergency department (ED) presentations. The resulting burden on health service costs and the potential impact of climate change is largely unknown. This study examines the temperature-EDs/cost relationships in Adelaide, South Australia and how this may be impacted by increasing temperatures. Methods: A time series analysis using a distributed lag nonlinear model was used to explore the exposure–response relationships. The net-attributable, cold-attributable and heat-attributable ED presentations for temperature-related diseases and costs were calculated for the baseline (2014–2017) and future periods (2034–2037 and 2054–2057) under three climate representative concentration pathways (RCPs). Results: The baseline heat-attributable ED presentations were estimated to be 3600 (95% empirical CI (eCI) 700 to 6500) with associated cost of $A4.7 million (95% eCI 1.8 to 7.5). Heat-attributable ED presentations and costs were projected to increase during 2030s and 2050s with no change in the cold-attributable burden. Under RCP8.5 and population growth, the increase in heat-attributable burden would be 1.9% (95% eCI 0.8% to 3.0%) for ED presentations and 2.5% (95% eCI 1.3% to 3.7%) for ED costs during 2030s. Under the same conditions, the heat effect is expected to increase by 3.7% (95% eCI 1.7% to 5.6%) for ED presentations and 5.0% (95% eCI 2.6% to 7.1%) for ED costs during 2050s. Conclusions: Projected climate change is likely to increase heat-attributable emergency presentations and the associated costs in Adelaide. Planning health service resources to meet these changes will be necessary as part of broader risk mitigation strategies and public health adaptation actions.